Wildlife Scientists : Reading and Understanding Graphs - Mcmillan, Dawn; Johson, Sara (Huntington Beach, CA : T Teacher Created Materials, 2008)
Wildlife scientists study animals and plants, and they learn about endangered animals and how to help save them. Many times animals are tagged to study them and track them. Dr. Ian Stirling studies polar bears and retrieves data by observing them throughout the year. Dr. Jane Goodall studied chimpanzees all her life and learned many interesting things about the way they live, which is much like humans. She believes that we can help animals and promote peace in the world.
Includes index and answer key
Keywords: Wildlife conservation -- Juvenile literature; Wildlife conservationists -- Juvenile literature; Charts, diagrams, etc. -- Juvenile literature